Kajian Stabilitas Fisikokimia Antibiotik β-laktam: Implikasi terhadap Formulasi dan Penyimpanan - Abu Dzar Alghifary; Nor Latifah (Lembaga Pengembangan Kinerja Dosen, 2025)
β-lactam antibiotics are a very important group of drugs and are most frequently used in the treatment of bacterial infections, both in healthcare facilities and for self-medication. The advantages of β-lactams lie in their effectiveness and broad spectrum of action. However, the development of pharmaceutical preparations containing β-lactams still faces significant challenges, particularly related to the physicochemical stability of these compounds. The reactive ring structure of β-lactams makes them highly susceptible to degradation, particularly through hydrolysis. This degradation process can be accelerated by various environmental factors such as high temperature, changes in pH, humidity, and the presence of certain excipients and solvents in drug formulations. This article comprehensively reviews the various factors that influence the stability of β-lactams, both in solid and liquid pharmaceutical dosage forms, as well as in microbiological media. Furthermore, it also examines various innovative formulation approaches that have been developed to improve the stability of these compounds. These approaches include film coating technology, encapsulation, and crystal engineering, which have been shown to reduce the rate of degradation and extend product shelf life. Literature studies have shown that solid dosage forms are generally more stable than liquid dosage forms, primarily because exposure to water and solvents can accelerate hydrolysis. Distribution and storage of these preparations are also important aspects to consider in maintaining the quality and effectiveness of β-lactam antibiotic therapy. Therefore, β-lactam product development requires a holistic approach, encompassing not only formulation and production technology but also optimal distribution and storage strategies. The use of appropriate analytical methods is also necessary to monitor degradation products and ensure product safety and effectiveness throughout the shelf life.